Antiferromagnetic ordering to cluster-glass like transition behavior in DyVO4 - Upadhyay R.; Shukla M.; Upadhyay C. (My University, 2025)
We herein present the detailed investigation of the structural and magnetic properties of the Jahn–Teller compound DyVO4 in otherwise reported as antiferromagnetic compound. The static and dynamic magnetic measurements reveal the emergence of cluster-glass like phase in DyVO4. The magnetization vs temperature measurement in field-cooling and zero-field-cooling shows irreversibility above Néel temperature as increasing the field above 1000 Oe, indicating the glass-like behavior in DyVO4. The frequency dependence of ac-susceptibility is analyzed by calculating the Mydosh parameter, which confirms the cluster-glass phase in DyVO4 at applied dc magnetic fields. The frequency dependence ac-susceptibility is also analyzed within the framework of dynamic scaling laws such as power law and Vogel–Fulcher law. The extracted parameters supports the fact that transitions are spin cluster-glass like. Further the memory effect establishes antiferromagnetic to spin cluster-glass like transition in DyVO4 conclusively. © 2022 Elsevier Ltd